2016
DOI: 10.1007/s00125-016-4000-x
|View full text |Cite|
|
Sign up to set email alerts
|

Non-metabolisable insulin glargine does not promote breast cancer growth in a mouse model of type 2 diabetes

Abstract: Aims/hypothesis Previous epidemiological studies have reported a potential link between insulin analogues and breast cancer; however, a prospective randomised controlled trial showed neutral effects of insulin glargine on cancer risk. Insulin glargine is metabolised in vivo to an M1 metabolite. A question remains whether a subset of individuals with slower rates of glargine metabolism or who are on high doses could, theoretically, have an increased risk of cancer progression if a tumour is already present. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…7 Effect on blood glucose, body weight gain and epididymal fat mass after treatment with vehicle (large circles), human insulin 600 nmol/kg (small circles) or X10 600 nmol/kg (diamonds) for 18 days. (a) Treatment with human insulin and X10 decreased blood glucose compared with vehicle, X10 more potently than human insulin, in agreement with the data describing the area above the blood glucose curve ( Table 5) Our findings are in clear contrast to recent studies, which reported that none of human insulin, X10 or a nonmetabolisable analogue of insulin glargine in suprapharmacological doses up to 1200 nmol/kg was able to activate the IGF-1R in normal rats and mouse allograft models [12][13][14][15]. However, there are several differences in methods between our study and the previous ones.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…7 Effect on blood glucose, body weight gain and epididymal fat mass after treatment with vehicle (large circles), human insulin 600 nmol/kg (small circles) or X10 600 nmol/kg (diamonds) for 18 days. (a) Treatment with human insulin and X10 decreased blood glucose compared with vehicle, X10 more potently than human insulin, in agreement with the data describing the area above the blood glucose curve ( Table 5) Our findings are in clear contrast to recent studies, which reported that none of human insulin, X10 or a nonmetabolisable analogue of insulin glargine in suprapharmacological doses up to 1200 nmol/kg was able to activate the IGF-1R in normal rats and mouse allograft models [12][13][14][15]. However, there are several differences in methods between our study and the previous ones.…”
Section: Discussionsupporting
confidence: 91%
“…A potential concern could be that growthstimulatory effects of insulin and X10 are masked by the hypoglycaemia. However, the original finding with X10 was in a 12 month chronic toxicity study performed in normal rats, which developed hypoglycaemia with each X10 treatment, and in several previous allograft experiments in normal mice, treatment with high doses of insulin and X10 increased tumour growth despite repeated reduction of blood glucose to a hypoglycaemic level, fully comparable with this study [12,13,18]. Furthermore, in the COLO-205 xenograft experiment performed in diabetic host animals, we explored the correlation between xenograft mass and the mean blood glucose during the experiment days and observed the largest tumours in the mice with the lowest blood glucose and a significant negative correlation between tumor mass and blood glucose, i.e.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations